Improved Dissolution and Pharmacokinetics of Abiraterone through KinetiSol® Enabled Amorphous Solid Dispersions - Urvi Gala; Dave Miller; Robert O. Williams (MDPI AG, 2020)
Abiraterone is a poorly water-soluble drug. It has a high melting point and limited solubility in organic solvents, making it difficult to formulate as an amorphous solid dispersion (ASD) with conventional technologies. KinetiSol® is a high-energy, fusion-based, solvent-free technology that can produce ASDs. The aim of this study was to evaluate the application of KinetiSol to make abiraterone ASDs. We developed binary KinetiSol ASDs (KSDs) using both polymers and oligomers. For the first time, we reported that KinetiSol can process hydroxypropyl-β-cyclodextrin (HPBCD), a low molecular-weight oligomer. Upon X-ray diffractometry and modulated differential scanning calorimetry analysis, we found the KSDs to be amorphous. In vitro dissolution analysis revealed that maximum abiraterone dissolution enhancement was achieved using a HPBCD binary KSD. However, the KSD showed significant abiraterone precipitation in fasted state simulated intestinal fluid (FaSSIF) media. Hence, hypromellose acetate succinate (HPMCAS126G) was selected as an abiraterone precipitation inhibitor and an optimized ternary KSD was developed. A pharmacokinetic study revealed that HPBCD based binary and ternary KSDs enhanced abiraterone bioavailability by 12.4-fold and 13.8-fold, respectively, compared to a generic abiraterone acetate tablet. Thus, this study is the first to demonstrate the successful production of an abiraterone ASD that exhibited enhanced dissolution and bioavailability.